Effects of fatigue on the neuromuscular capacity of professional soccer players - Moreira, Pedro V.S. [UNESP]; Gonçalves, Mauro [UNESP]; Luciano, F. C. [UNESP]; Castro, Alex [UNESP]; Neto, Antônio F. Almeida [UNESP]; Goethel, Márcio F. [UNESP]; Cardozo, Adalgiso C. [UNESP] (SAGE Publications, 2015)
BACKGROUND: Hamstrings:quadriceps (H:Q) strength muscular imbalances are frequently associated with injuries. OBJECTIVE: To investigate the H:Q ratio dependencies of the fatigue effect induced by an exhaustive isokinetic exercise. METHODS: Nineteen male soccer players were evaluated, before and after exhaustive isokinetic exercises, for electromechanical delay (EMD), root mean square (RMS), median frequency (MF), and rate of electromyographic rise (RER) of the rectus femoris (RF), vastus lateralis (VL), vastus medialis (VM), biceps femoris (BF), semitendinosus (ST), isometric peak torque (PT) and rate of torque development (RTD) of the knee extensors (KE) and knee flexors (KF). The fatigue effect was measured by paired dependent tests, with a significance level of p < 0.05. RESULTS: RTD and PT were reduced (23-38%), with an H:Q reduction of RTD100 ms by 21%. In PT, antagonist RMSVL and RMSRF decreased by 32-39%, but at 0-50 ms, 0-100 ms and 0-200 ms, agonist RMSRF diminished by > 32%. At 0-50 ms and 0-100 ms, the antagonist RMSVM improved by > 149%. RERRF and RERST diminished in both 0-50 ms and 0-100 ms (38-41%), while RERBF decreased at 0-50 ms (30%). Agonist MFRF and MFBF in PT decreased by 9-10%. CONCLUSION: Neuromuscular fatigue due to maximal isokinetic concentric voluntary contractions affects the hamstrings more than the quadriceps in terms of producing rapid torque.
Keywords: electromyography; hamstring-quadriceps ratio; Isokinetic; isometric contraction; torque